Instability and internet design - Sandra Braman (Internet Policy Review, 2016)
Instability - unpredictable but constant change in one's environment and the means with which one deals with it - has replaced convergence as the focal problem for telecommunications policy in general and internet policy in particular. Those who designed what we now call the internet during the first decade of the effort (1969-1979), who in essence served simultaneously as its policy-makers, developed techniques for coping with instability of value for network designers today and for those involved with any kind of large-scale sociotechnical infrastructure. Analysis of the technical document series that was medium for and record of that design process reveals coping techniques that began with defining the problem and went on to include conceptual labour, social practices, and technical approaches.
Keywords: 300; Internet design; Sociotechnical decision-making; Resilience